2019
DOI: 10.1111/1756-185x.13741
|View full text |Cite
|
Sign up to set email alerts
|

Association analysis of interleukin‐23 receptor SNPs and SAPHO syndrome in Chinese people

Abstract: Objective: SAPHO syndrome (synovitis, acne, pustulosis, hyperostosis, and osteitis) is an autoimmune disease of unknown etiology that seriously affects patients' daily lives. Family-based investigations support genetic contributions toward disease susceptibility. The present study evaluated whether the previously reported autoimmune disease-associated single nucleotide polymorphisms (SNPs) have any genetic overlap with SAPHO syndrome. Method:Genomic DNA was obtained from 71 SAPHO patients and 104 healthy contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…1,2 Variants rs10889677, rs2201841, rs7517847 of IL-23R and rs2243248 of IL-4 showed strong associations with SAPHO syndrome. 3 Our results for rs7517847 of IL-23R and rs2243248 of IL-4 were similar to Guo's results. However, more studies are required to further explore our findings.…”
Section: The Role Of Genetic Factors and Peripheral Immune Cells In Sapho Syndromesupporting
confidence: 90%
See 1 more Smart Citation
“…1,2 Variants rs10889677, rs2201841, rs7517847 of IL-23R and rs2243248 of IL-4 showed strong associations with SAPHO syndrome. 3 Our results for rs7517847 of IL-23R and rs2243248 of IL-4 were similar to Guo's results. However, more studies are required to further explore our findings.…”
Section: The Role Of Genetic Factors and Peripheral Immune Cells In Sapho Syndromesupporting
confidence: 90%
“…Recently, pathogenesis of DSAP was elucidated by detecting MVK, PMVK, MVD and FDPS loss-of-function mutations in patients with familiar or sporadic porokeratosis. [3][4][5][6] The mutated genes are involved in mevalonate pathway. After a second-hit mutation, it is assumed that the diminished final products of mevalonate pathway together with the accumulation of toxic metabolites result in the clinical phenotype of DSAP.…”
Section: The Role Of Genetic Factors and Peripheral Immune Cells In Sapho Syndromementioning
confidence: 99%
“…Studies have shown that variants rs10889677, rs2201841, and rs7517847 of IL-23R, and variant rs2243248 of IL-4, showed strong associations with SAPHO syndrome. Patients carrying the A-G-C-G-T haplotype of IL-23 are significantly more likely to develop SAPHO syndrome ( 92 ).…”
Section: Roles Of Pstpip2 In Inflammatory Diseasesmentioning
confidence: 99%
“…Previous research reported that the dysregulation of interleukin-1 (IL-1) signaling promoted sterile osteomyelitis in Pstpip2-deficient mice (Ferguson et al, 2006;Sharma and Ferguson, 2013). However, no specific variants were found using genetic screening in the PSTPIP1, PSTPIP2, NOD2 or LPIN2 genes in SAPHO samples (Hurtado-Nedelec et al, 2010;Colina et al, 2012;Guo et al, 2019). There are several factors considered to have the role in the development of SAPHO syndrome, including Propionibacterium acnes infection (Kotilainen et al, 1996;Colina et al, 2007), impaired immune responses, over-activated TH17…”
Section: Introductionmentioning
confidence: 99%